Pengaruh Word of Mouth dan E-Commerce Terhadap Peningkatan Pendapatan Menurut Perspektif Ekonomi Islam - Muhammad Suhaidi; Desi Nurhabibah; Estelee Elora Akbar; Muhammad Iskandar (ITB AAS INDONESIA Surakarta, 2022)
Income is a very important element in a trading business, because in doing a business, of course you want to know the value or amount of income earned during the business. In an economic sense, income is remuneration for the use of production factors owned by the household sector and the corporate sector which can be in the form of salaries/wages, rent, interest and profits/profits. The formulation of the problem in this study is how word of mouth and e-commerce partially and simultaneously affect the increase in income, how word of mouth and e-commerce affect the increase in income according to the Islamic Economic Perspective. The purpose of this study was to determine and analyze word of mouth and e-commerce have a positive effect on increasing revenue partially and simultaneously and to determine and analyze word of mouth and e-commerce on increasing income in the Islamic Economic Perspective. This research methodology uses quantitative methods. Sources of primary data and secondary data. The sample in this study amounted to 30 employees at Yummy Pie as respondents using a sampling technique. By using validity test, reliability test and prerequisite test using normality test and multicollinearity test. The data analysis process uses multiple linear regression analysis with SPSS 20 data processing tools. The results in the study partially show that the word of mouth variable has no significant effect on increasing income, e-commerce has a positive effect on increasing income at yummy pie in Bandar Lampung City. The results of the study simultaneously show that word of mouth and e-commerce variables have a significant effect on increasing income at yummy pie in Bandar Lampung City. The result of the analysis of the determinant coefficient of R-Squared is 0.225. This means that the variance and word of mouth and e-commerce are able to explain the variance of 22.5% while the remaining 77.5% is explained by other variables outside the study.